(3Mbhb hVeGfGJ GdSLjf aj Xd GdbGfhfjf GdhWfj hGdOhdj (B:s (3OQGSI ebGQfI (B/s - (3jhfS eMeO jhfS CMeO GdTjNs; (3YeQ eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2025)
(3hbO JfGhd GdHMK HYeb hJaUjd GdJTQjYGJ GdMOjKI hhSGFd JWhjQ JfajP GdYbhHI HYO XghQ GdeHGOF GdYbGHjI GdJj dYHJ OhkQG egeG aj JWhjQ JfajP GdYbhHI hVeGfGJ hMbhb GdfRdGA (B. (3hJbOje cGaI CfhGY GdQYGjI ShGA GdUMjI Ch GdGLJeGYjI Ch GdJYdjejI, HYO XghQ GdGJLGgGJ GdMOjKI GdJj JOYh Edi GdMaGX Ydi MQjI GdEfSGf hcQGeJg HTcd YGe hcQGeI GdfRjd CKfGA JfajP YbhHJg, hgh eG GfYcS HOhQg aj GdehGKjb hGdGJaGbjGJ GdOhdjI eKd EYdGf Mbhb GdEfSGf, hbhGYO fjdShf eGfOjdG, hGdbhGYO hGdePGgH GdacQjI GdeYGUQI GdJj GYJeOJgG GdYOjO ef GdJTQjYGJ GdhWfjIs
The research dealt in depth and detail with modern legislation and means of developing the implementation of punishment after the emergence of penal principles, which played an important role in developing the implementation of punishment and the guarantees and rights of prisoners. Providing all types of care, whether health, social or educational
(3CWQhMI (B((3OcJhQGI(B)(3, LGeYI GdbGgQI, cdjI GdMbhb , bSe GdbGfhf GdLfGFj (B2025s
(3HHdjhLQGajG(B: (3UaMGJ (B399-435s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdYbhHIs; (3fXGe GdaMU hGdJUfjas; (3GdYed GdYbGHjs; (3GdYed GdYbGHjs; (3VeGfGJ GdeMche Ydjgs; (3fXQjI GdGfGHIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs